Performance management and appraisal systems : HR tools for global competitiveness - Rao, T. Venkateswara (New Delhi ; Thousand Oaks : Response Books, a division of Sage Publications, 2004)
The book explores the many facets of performance management and how it works as well as extends it to encompass individuals, dyads and teams.
Includes bibliographical references (p. [313]-317) and index.
uaj 23/09/2014
Loan
Keywords: Personnel management; Performance - management; Employees - rating of; Appraisal system